ONECUT2-driven activation of ADAMTS14 boosts colorectal cancer stemness via Wnt pathway - Jiang, Yicheng; Tan, Xingping (Human cell : official journal of Human Cell Research Society, 2025)
The malignant progression of colorectal cancer (CRC) is closely related to cell stemness, but its regulatory mechanism has not been fully elucidated. This study found that ADAMTS14 was significantly highly expressed in CRC tissues and cell lines and was associated with poor prognosis in patients. Functional experiments have confirmed that ADAMTS14 enhances the stemness characteristics (such as upregulation of ALDH1A1, ALDH1A3, and CD133 expression) and spheroidization ability of CRC cells by activating the Wnt signaling pathway. Further mechanism studies have shown that the transcription factor ONECUT2 is also highly expressed in CRC and indicates a poor prognosis, and it can directly activate its transcription by binding to the ADAMTS14 promoter region. In conclusion, this study has revealed a novel mechanism by which the ONECUT2/ADAMTS14/Wnt axis regulates the stemness of CRC cells, providing a potential molecular target for targeted intervention.